P16 | A 3D IN VITRO MODEL TO STUDY CAF PLASTICITY AND TUMOR-STROMA INTERACTIONS IN OVARIAN CANCER (European Journal of Histochemistry)
The tumor microenvironment (TME) plays a pivotal role in cancer progression and therapy resistance. Among its components, cancer-associated fibroblasts (CAF) are key players in remodeling the extracellular matrix, promoting tumor invasion, and modulating immune responses. In this context we developed a robust 3D in vitro model of ovarian cancer, integrating cancer cells and stromal components to recreate key structural and functional aspects of the human TME. Using heterotypic tumor spheroids composed of ovarian cancer cell lines and stromal cells, we recreated a relevant microenvironment to investigate CAF-like cell behavior. Human dermal fibroblasts were exposed to tumor cell-conditioned media, with or without TGF-β, to induce CAF-like phenotypes. Our findings demonstrate that distinct microenvironmental stimuli drive the emergence of heterogeneous CAF-like populations, which in turn influence spheroid properties. This 3D model recapitulates key features of the reactive stroma and enables functional analysis of tumor-stroma crosstalk under controlled conditions. It provides a robust platform for mechanistic studies and therapeutic investigation, offering new opportunities to dissect the dynamic interactions within the ovarian tumor microenvironment.